REGULARITIES OF VISCOSITY FORMATION OF CONDENSED FAT-FREE MILK WITH SUGAR FROM HEAT TREATMENT PARAMETERS - Aram G. Galstyan; Iskra A. Radaeva; Sergei A. Khurshudyan; Svetlana N. Turovskaya; Vladislav K. Semipyatniy; Elena E. Illarionovа (Пищевые системы, 2018)
Structural and mechanical properties of condensed milk preserves, including viscosity, depend on many factors (the type and composition of the raw dairy raw materials, processing techniques, conditions and shelf life, etc.) and through the organoleptic characteristics determine the consumer properties of the products.The article presents the study results of the influence of the heat treatment modes of fat-free milk before thickening on the viscosity of the finished product. Were studied freshly processed and after storage samples of condensed fat-free milk with sugar, for the development of which was used laboratory equipment, which allows reproducing the main technological operations for obtaining condensed milk preserves with sugar. Seven samples of condensed fat-free milk with sugar were obtained at three temperatures of pasteurization 75 °C, 85 C and 95 °C with a holding time of 15 s, 10 and 30 min. Were determined dynamic viscosity, active and titratable acidity in the samples. it is shown that in freshly processed products the temperature of 75 °C with the exposure from 15 s to 30 min did not lead to a significant increase in the viscosity of the samples. The thermal regime of 95 °C with an exposure of 15 s caused the viscosity to increase up to 1.9 Pa·s. The thermal regime of 85 °C for 30 min led to an even greater increase in viscosity, up to 2.5 Pa·s. An assumption was made on the formation of interrelations “pasteurization temperature — viscosity”. The analysis of the results of the change in the effective dynamic viscosity as a function of the shear gradient in the specified samples subjected to storage under extreme temperature conditions were carried out. The obtained regularities are mathematically processed and presented in the form of spatial diagrams and formulas. Recommendations are given for the most appropriate modes of heat treatment of fat-free milk, which least influences the viscosity increase of the product during storage.